(untitled) (Research, Society and Development, 2020)
Introduction: Hypertrophy of the temporal muscle is rare, and can be caused by a variety of factors, such as congenital causes or even acquired through hyperactivity of the masticatory muscles. Causing the muscle in question to develop excess muscle tissue by altering the facial contour generating aesthetic complaints for many patients. Objective: This study aimed to address the treatment of temporal muscle hypertrophy with botulinum toxin. The research is justified by the importance of knowing this treatment in view of the rarity of the case. Methodology: The methodology was integrative research based on scientific articles and a clinical case report. Therefore, the use of botulinum toxin in the field of Dentistry has become effective in the treatment of rehabilitation in patients with temporal muscle hypertrophy, providing aesthetic and functional improvement for the patient and may involve multidisciplinary therapy covering Orthodontics and Psychology.